1
$\begingroup$

I have an input signal $$x(n)=\left(3,-5,4,3,-1,-2,6,8\right), n=-3,..,4$$ and impulse response $$h(n)=(1,-1,1,-1,1), n=-1,...,3.$$

The convolution between $x(n)$ and $h(n)$ is

$$x(n)*h(n)=\sum_{-\infty}^\infty x(k)h(n-k)$$ If I'm not mistaken, I can reduce this to the finite sum $$=x(-3)h(n+3)+x(-2)h(n+2)+x(-1)h(n+1)+x(0)h(n)+x(1)h(n-1)+x(2)h(n-2)+x(3)h(n-3)+x(4)h(n-4)$$

So, if I were to calculate the sum by hand, I would proceed by first evaluating

$x(-3)h(n+3)=3h(n+3) = (3,-3,3,-3,3)$ for $n=-4,...,0$ $x(-2)h(n+2)=-5h(n+3) = (-5,+5,-5,+5,-5)$ for $n=-3,...,1$
etc...

Then I would only add up the terms whose position $n$ aligns (that is, add all terms at n=-4 together, all terms at n=-3 together, etc...).

Is my approach to evaluating the convolution correct?

$\endgroup$
3
$\begingroup$

I would have liked to give a longer answer, but yes, your approach is correct. I don't see any problems with what you laid out in your question.

$\endgroup$
  • $\begingroup$ No worries... That's all I was looking for :) $\endgroup$ – Paul Oct 3 '12 at 2:18
  • $\begingroup$ Is there any other approach to compute the same quantities manually? $\endgroup$ – Paul Oct 3 '12 at 2:23
  • 1
    $\begingroup$ @Paul You may learn at a later date about transform methods and the like which provide a different way of computing, but there is little else to be done except what you have for a manual approach. Also, see the second half of this answer to a different question on this site, which also lays out a similar calculation using a tabular approach. $\endgroup$ – Dilip Sarwate Oct 3 '12 at 2:44

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.